Macromol. Mater. Eng. 10/2016. Issue 10 (October 2016) - Ruediger, Arne A.; Bremser, Wolfgang; Strube, Oliver I.
Abstract : Front Cover: Enzyme‐mediated autodeposition enables defined and biocompatible addressing of particles on surfaces. Depending on the enzyme mobility, diverse structures can be obtained: from micrometer coatings down to the arrangement of single nanoparticles. Promising applications are found in the areas of biomaterials and nanoelectronics. Further details can be found in the article by Arne A. Ruediger, Wolfgang Bremser, and Oliver I. Strube* on page 1181.